PERAN STAKEHOLDER TERHADAP KUALITAS PERENCANAAN STRATEGIS DI SMK KP BALEENDAH - Teti Ratnawulan; Winda Wulandari; Fitrianingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Strategic planning in vocational schools (SMK) is a crucial aspect in improving educational quality, involving various stakeholders such as school principals, teachers, parents, and industry. This study aims to analyze the role of stakeholders in the quality of strategic planning at SMK KP Baleendah, Bandung Regency. The research method used is qualitative descriptive, with data collection techniques through interviews, observation, and documentation. The findings show that stakeholder involvement at SMK KP Baleendah is already relatively high, but there are still challenges in communication and limited facilities. A SWOT analysis was conducted to explore the strengths, weaknesses, opportunities, and threats faced by the school. Key strengths include the school's reputation, foundation support, efficient management, and adequate facilities, while weaknesses include communication challenges and limited resources. Development opportunities include enhancing teacher skills and expanding partnerships with industry, while the main threats are leadership transitions and potential internal conflicts. The results of this study are expected to provide insights for other vocational schools to improve stakeholder participation in strategic planning to create more relevant and high-quality education.